PERAYAAN PERINGATAN KEDATANGAN BAHARIWAN CHENG HO DAN PERANNYA PADA PERKEMBANGAN PARIWISATA DI SEMARANG - Conny Handayani (Humaniora, 2006)
Every year, the Indonesian Chinese and the native Javanese always commemorate the coming of Admiral Cheng Ho (well-known as Sam Po Kong or Sam Po Thay Jien) to the Indonesian Archipelago and especially to Central Java. For political reasons, President Soeharto through his decree No.14/1967 forbade all the Chinese tradition, cultural and religious activities. Before Soeharto’s government, this Sam Po Kong Festival was celebrated by the pilgrims who came from all over the world. In Soeharto’s time this ceremony was forbidden, too. President Abdurrahman Wahid and President Megawati have issued decrees which allow the Indonesian Chinese to celebrate their tradition and to worship their beliefs freely. This positive situation brings good result to Tourism Industry in Central Java and is considered as “A Blessing in Disguise” especially to Indonesian people and especially to the peole living in Semarang which hasa lot of Chinese Inheritance